Paradigma Pendidikan Islam - Yahdi, Muhammad (Inspiratif Pendidikan, 2016)
Education, particularly Islamic education, develops and changes dealing with the implementation of learning methodology. These developments always follows students’ problems and needs as well as human civilization development. The students who have the information accesses require learning methodologies that can fulfill the needs and develop the information obtained learners. Learning always refers to students as an effort to increase knowledge, broaden the analysis and shaping personality. The goals will be important to develop self-learners themselves facilitated by the teachers.